Evaluation of the Diagnostic Performance of Positron Emission Tomography/Magnetic Resonance for the Diagnosis of Liver Metastases. Issue 10 (October 2021) - Zhang, Caiyuan; O'Shea, Aileen; Parente, Chiara Anna; Amorim, Barbara Juarez; Caravan, Peter; Ferrone, Christina R.; Blaszkowsky, Lawrence S.; Soricelli, Andrea; Salvatore, Marco; Groshar, David; Bernstine, Hanna; Domachevsky, Liran; et al.
Abstract : Objective: The aim of this study was to compare the performance of positron emission tomography (PET)/magnetic resonance (MR) versus stand-alone PET and stand-alone magnetic resonance imaging (MRI) in the detection and characterization of suspected liver metastases. Materials and Methods: This multi-institutional retrospective performance study was approved by the institutional review boards and was Health Insurance Portability and Accountability Act compliant, with waiver of informed consent. Seventy-nine patients with confirmed solid extrahepatic malignancies who underwent upper abdominal PET/MR between February 2017 and June 2018 were included. Where focal hepatic lesions were identified, the likelihood of a diagnosis of a liver metastasis was defined on an ordinal scale for MRI, PET, and PET/MRI by 3 readers: 1 nuclear medicine physician and 2 radiologists. The number of lesions per patient, lesion size, and involved hepatic segments were recorded. Proof of metastases was based on histopathologic correlation or clinical/imaging follow-up. Diagnostic performance was assessed using sensitivity, specificity, positive and negative predictive values, and receiver operator characteristic curve analysis. Results: A total of 79 patients (53 years, interquartile range, 50–68; 43 men) were included. PET/MR had a sensitivity of 95%, specificity of 97%, positive predictive value of 97%, and negative predictive value of 95%. The sensitivity, specificity, positive predictive value, and negative predictive value of MRI were 88%, 98%, 98%, and 90% and for PET were 83%, 97%, 97%, and 86%, respectively. The areas under the curve for PET/MRI, MRI, and PET were 95%, 92%, and 92%, respectively. Conclusions: Contrast-enhanced PET/MR has a higher sensitivity and negative predictive value than either PET or MRI alone in the setting of suspected liver metastases. Fewer lesions were characterized as indeterminate by PET/MR in comparison with PET and MRI. This superior performance could potentially impact treatment and management decisions for patients with suspected liver metastases.